A possible link between luteinizing hormone and macrophage migration inhibitory factor levels in polycystic ovary syndrome. (2nd July 2016) - Calan, Mehmet; Kume, Tuncay; Yilmaz, Ozgur; Arkan, Tugba; Kocabas, Gokcen Unal; Dokuzlar, Ozge; Aygün, Kemal; Oktan, Mehmet Asi; Danıs, Nilay; Temur, Muzaffer
ABSTRACT: Purpose: Macrophage migration inhibitory factor (MIF) is a multifunctional cytokine that plays a role in metabolic and inflammatory processes. Increasing evidence suggests that there is a link between MIF and ovulation. We aimed to evaluate plasma MIF levels in women with polycystic ovary syndrome (PCOS) and to determine whether MIF levels differ between the follicular phase and mid-cycle of the menstrual cycle in eumenorrheic women.Methods: Ninety women with PCOS and 80 age- and BMI-matched healthy eumenorrheic women were consecutively recruited into this prospective observational study. For all subjects, plasma MIF levels in the early follicular phase were measured by ELISA; for the 40 healthy controls, MIF levels were also measured during mid-cycle of the same menstrual cycle.Results: Plasma MIF levels were significantly higher in women with PCOS than in eumenorrheic women (14.16 ± 1.59 vs. 10.39 ± 0.70 ng/ml; p < 0.001). MIF levels were significantly higher at mid-cycle than in the follicular phase in eumenorrheic women (11.15 ± 0.61 vs. 10.56 ± 0.82 ng/ml; p < 0.001). MIF was positively correlated with BMI, high sensitivity C-reactive protein (hs-CRP), and homeostasis model assessment of insulin resistance (HOMA-IR) in both groups. MIF was positively correlated with luteinizing hormone (LH) and free-testosterone only in the PCOS group. Binary logistic regression analyses revealed that the odds ratio (OR) for PCOS independently increases linearly with elevated MIF (OR = 1.385, 95% CI = 1.087–1.764, p = 0.017).Conclusion: MIF may play a crucial role in the reproductive system in women, including the development of PCOS and normal ovulation.